SAT0345 Histopathological Differences between Single-Organ Cutaneous Small Vessel Vasculitis and Other Cutaneous Vasculitis Associated with Systemic Involvement. (15th July 2016) - Fernández-Díaz, C.; Loricera, J.; González-Vela, C.; Blanco, R.; Hernández, J.L.; González-Lόpez, M.A.; Armesto, S.; Salcedo, W.; Marcellán, M.; Lόpez-Escobar, M.; Lacalle-Calderόn, M.; Calvo-Río, V.; et al.
Abstract : Background: Cutaneous vasculitis (CV) encompasses a wide and heterogeneous group of disorders characterized by the presence of necrotizing inflammatory lesions in the cutaneous blood vessels. Single-organ cutaneous small vessel vasculitis (SoCSVV) is, according to 2012 Chapel-Hill criteria, a vasculitis confined to the skin. Objectives: Our aim was to compare the histopathological findings of skin biopsies from patients with SoCSVV and those with systemic involvement. Methods: From a series of patients with CV, we selected 3 groups: group a) SoCSVV; group b) CV with systemic involvement; group c) subgroup of patients of group b with involvement of 3 organs other than the skin. A comparative study between the group a) with the other two groups (b and c) was performed. Results: Group a) was integrated by 9 patients (7 W/2 M; mean age, 64±16 years). In the group b) 43 patients were included (18 W/25M; mean age, 54±21 years). The underlying conditions were: severe bacterial infections (n=12), hypersensitivity vasculitis with involvement of other organs besides the skin (n=10), HSP (n=9), panarteritis nodosa (n=4), microscopic polyangiitis (n=2), cryoglobulinemia (n=2), malignancy (n=2), SLE (n=1) and Sjögren's syndrome (n=1). Finally, 7 patients (3 W/4 M; mean age, 50 ± 20 years) were included in group c) . The underlying conditions were: severe bacterial infections (n=3), HSP (n=3) and cryoglobulinemia (n=1). The results of histopathological comparison of group a) with the groups b) and c) are shown in the table. Although no parameter reached statistical significance, in our series we observed that the greater systemic involvement was more frequently associated with tissue neutrophilia, pustular dermatosis and deep involvement of arterioles. By contrast, SoCSVV tend to develop greater tissue eosinophilia and tissue lymphocytosis, whilst the intensity of the inflammatory infiltrate was lower. On the other hand, none of the samples of patients with SoCSVV showed involvement of deep arterioles. Conclusions: In this series we observed that qualitative and quantitative histological differences were correlated with the degree of systemic involvement. However, these results need to be tested in prospective studies with a larger number of patients. Acknowledgement: "Fondo de Investigaciones Sanitarias" PI12/00193 (Spain) and RETICS Programs, RD08/0075 (RIER) and RD12/0009/0013 from "Instituto de Salud Carlos III" (ISCIII) (Spain). Disclosure of Interest: None declared